Nursing satisfaction after standardizing the chronic wounds care - Francisco José García Sánchez; Elena González Urraca; Francisco López Salazar; Mª Carmen Martínez García; Mª Pilar Romero Valverde; José María Flores López-Ibarra (Fundación para el Desarrollo de la Enfermería, 2009)
The Management of Primary Attention of Ciudad Real and the Management of Area of Puertollano elaborated, jointly during year 2005, Manual in Prevention and a Treatment of Chronic Wounds with the objective to standardize and to protocol the welfare practice in this matter. During the month of February of 2006 an anonymous survey with 6 questions is elaborated to know the satisfaction the professionals after the implantation of this tool, presented/displayed a cross-sectional descriptive study that throws the following global results: The necessity to implant a manual is valued with 8,97 on 10. The format of pocket chosen for the manual is valued with 8,94 on 10. The presentation of the manual is valued with 8.88 on 10. Speakers are valued with 8,63 on 10. The contents of the manual obtain a score of 8.90 on 10. The utility of the manual is valued with 8.87 on 10.The results indicate that the professionals demanded a tool that standardized the clinical practice in the prevention and treatment of chronic wounds. It seems to be that it has been guessed right in the format of the same one (pocket) and emphasizes the utility that they give the same one, although statistically significantly appear differences between both managements.